Analysis of Techniques and Quality of Translation of Surah Yasin into Rejang Language - Sakut Anshori; Muhammad Taqiyuddin; Rizki Indra Guci; Diana Hardiyanti (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
This study investigated the translation of Surah Yasin from Arabic into the Rejang language, focusing on translation techniques and quality. The objective was to evaluate how meaning was preserved and conveyed through this localized translation. The research involved a content analysis of the translated work titled Alquran Ngen Tai Ne Lem Baso Jang and was complemented by Focus Group Discussions (FGDs) with two expert raters and members of the translation team. The primary participants were seven Rejang language translators from IAIN Curup, each contributing their linguistic and religious expertise. The researchers adopted a qualitative descriptive approach, utilizing document analysis and FGDs to gather data, and applied Miles and Huberman's interactive model for analysis. Findings revealed that the most frequently used translation technique was “established equivalent” (64.08%), followed by explicitation (16.54%) and addition (5.94%), reflecting efforts to ensure clarity and contextual understanding. The translation quality scored an average of 2.95 out of 3, with high readability (3.00) and acceptability (2.98), though accuracy (2.93) showed room for refinement. These findings imply that localized religious translations, when done thoughtfully, can maintain both theological integrity and cultural relevance, thus aiding comprehension among minority language speakers.